(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article is devoted to the study of the problems of qualification of war crimes that cause damage to property. It is established that the qualification of seizure by a combatant of property belonging to the opposing parties is influenced by two key features: 1) the legal status of the property, type of ownership; 2) the purpose of seizure of such property. Such seizure of property of the opposing party, which becomes the state (state property of the opposing party) and is intended to use it for military purposes, is recognized as lawful. In other cases, a war crime will occur, provided for in Part 1 of Article 1 of Article 438 of the Criminal Code of Ukraine. The characteristic of the corresponding segment of the international legal conventual framework, to which the disposition of Part 1 of the specified article refers, is given. The features of the qualification of seizure by a combatant of property belonging to his own army, as well as unlawful actions with the property of civilians committed in the context of an armed conflict, are clarified. Criteria have been developed for distinguishing lawful damage or destruction of property in the context of an armed conflict (collateral damage) from unlawful, war crime.